Pengaruh Bauran Pemasaran 7P Terhadap Loyalitas Konsumen Pembelian Tanaman Hias Philodendron di PT. Berkah Melano Indonesia - Permata Dewi, Raddin Syabania; Mariyono, Joko; Santoso, Siswanto Imam (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
PT. Berkah Melano Indonesia operates in the buying and selling of ornamental plants, particularly philodendron plants, which are frequently repurchased. This study aims to analyze consumer loyalty levels and the impact of the 7P marketing mix on consumer loyalty in purchasing philodendron ornamental plants at PT. Berkah Melano Indonesia. The research was conducted at PT. Berkah Melano Indonesia, located in Cigugur Girang, Bandung. The study employed a case study method, with a sample of 100 respondents selected using quota sampling. The data analysis method used the consumer loyalty pyramid, which consists of switcher buyers, habitual buyers, satisfied buyers, liking the brand, and committed buyers, along with multiple linear regression analysis. The results indicate a high level of consumer loyalty, with 83.5% committed buyers, 83% liking the brand, 94% satisfied buyers, 76% habitual buyers, and 46% switcher buyers. The variables of product, price, place, people, and income partially influence consumer loyalty in purchasing philodendron ornamental plants at PT. Berkah Melano Indonesia. However, process and physical evidence do not have a partial impact on consumer loyalty in purchasing philodendron ornamental plants at the company. A recommendation for future research is to further examine the influence of process and physical evidence to determine whether these two variables consistently do not affect consumer loyalty. Additionally, the company should continue to maintain product quality, affordable pricing, easy platform access, enhanced promotions, and employee responsiveness in assisting consumers.